In their own voices: rural African American youth speak out about community-based HIV prevention interventions. - Coker-Appiah, Dionne Smith; Akers, Aletha Y; Banks, Bahby; Albritton, Tashuna; Leniek, Karyn; Wynn, Mysha; Youmans, Selena E; Parker, Donald; Ellison, Arlinda; Henderson, Stacey; Stith, Doris; Council, Barbara; et al. (Progress in community health partnerships : research, education, and action, 2009)
The HIV epidemic is a major public health problem in the United States, particularly among rural African American adolescents and young adults.
Keywords: Adolescent; Adult; African Americans; Community Networks; Community-Based Participatory Research; Female; Focus Groups; Health Education; Health Knowledge, Attitudes, Practice; Health Status Disparities; HIV Infections; Humans; Male; North Carolina; Program Evaluation; Qualitative Research; Risk Reduction Behavior; Rural Health Services; United States; Young Adult